Raman Microspectroscopy Goes Viral: Infection Dynamics in the Cosmopolitan Microalga, Emiliania huxleyi - Yakubovskaya, Elena; Zaliznyak, Tatiana; Martínez, Joaquín Martínez; Taylor, Gordon T. (Frontiers in Microbiology, 2021)
Emiliania huxleyi is a cosmopolitan member of the marine phytoplankton. This species’ capacities for carbon sequestration and sulfur mobilization make it a key player in oceanic biogeochemical cycles that influence climate on a planetary scale. Seasonal E. huxleyi blooms are abruptly terminated by viral epidemics caused by a clade of large DNA viruses collectively known as coccolithoviruses (EhVs). EhVs thereby mediate a significant part of material and energy fluxes associated with E. huxleyi population dynamics. In this study, we use spontaneous Raman microspectroscopy to perform label-free and non-invasive measurements of the macromolecular composition of individual virions and E. huxleyi host cells. Our novel autofluorescence suppression protocol enabled spectroscopic visualization of evolving macromolecular distributions in individual E. huxleyi cells at different stages of EhV infection. Material transfer from E. huxleyi hosts to single EhV-163 virions was confirmed by combining stable isotope probing (SIP) experiments with Raman microspectroscopy. Inheritance of the host cells’ 13C-enriched isotopic signature was quantified based on red shifts of Raman peaks characteristic of phenylalanine’s phenyl ring. Two-dimensional Raman mapping of EhV-infected E. huxleyi cells revealed that the compact region producing an intense Raman DNA signal (i.e., the nucleus) in healthy E. huxleyi cells becomes diffuse during the first hours of infection. Raman DNA emissions integrated throughout individual cells decreased during the infection cycle. Our observations are consistent with EhV-163 degrading the host’s nuclear DNA, scavenging released nucleotides for its own genome replication, and shedding newly-produced virions prior to host lysis via budding.